An Improved Technique Based on Firefly Algorithm to Estimate the Parameters of the Photovoltaic Model - Abed, Issa Ahmed (Iraqi Journal for Electrical and Electronic Engineering, 2017)
This paper present a method to enhance the firefly algorithm by coupling with a local search. The constructed technique is applied to identify the solar parameters model where the method has been proved its ability to obtain the photovoltaic parameters model. Standard firefly algorithm (FA), electromagnetism-like (EM) algorithm, and electromagnetism-like without local (EMW) search algorithm all are compared with the suggested method to test its capability to solve this model.